Personalism in the theological anthropology of E. Brunner and in the sophiology of revd. Sergei Bulgakov - Maxim Pylaev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The article is devoted to a comparative analysis of the personalist interpretation of the Christian kerygma in the dialectical theology of Protestantism (by E. Brunner) and in the Orthodox sophiological theology of the late S. Bulgakov. The author is interested in the problem of coherence of different forms of philosophical discourse, primarily metaphysical and non-metaphysical, within the framework of explication of the essence of Christianity. To what extent is the metaphysics of Plato and St. Gregory Palamas in the doctrine of Sophia by Rev. Sergei Bulgakov can coexist with the communicative, dialogic nature of the personality of F. Ebner and K. Jaspers? The article for the first time in Russian philosophical theology reconstructs the anthropology of E. Brunner, explores such concepts as "responsibility", "being-in-God", "being-in-decision" and others. The author compares E. Brunner's and K. Barth's conceptions of the Word of God. E. Brunner does not use metaphysics as the prerequisite for ontology. Being for him has a dialogical structure of the relationship (I and You) of man and God, the call to love and the response to love in the responsibility of man. Brunner defines human creation as 'creation in the Word of love'. "With this Word God addresses man, communicates himself to him, gives him life". The existential dimension of divine love is devoid of a cosmic dimension in the Swiss theologian and is not connected with the knowledge of the world in the natural sciences and metaphysics. He is indifferent to the objective aesthetics of the divine love kenosis. God for Brunner is understood primarily as love. It is the baseless mystery of God – the Word, eternally calling for a decision, responsibility, choice. E. Brunner's personalism looks more holistic, organic, thought out in its own way within the framework of modern philosophy. However, the extra-moral nature of human responsibility is not entirely obvious. It is difficult to imagine Christian love as an indicative and not an imperative. By the late S. Bulgakov, love belongs to the core of personality as activity. Absolute personality constitutes itself not as self-knowledge, but as active love. Love is not a property of the essence, but the essence itself. The Russian philosopher ontologizes love within the metaphysics of unity. S. Bulgakov interprets person's activitiestic principle and personality as a relationship from the perspective of rethinking the work-action of I. Fichte within the framework of the metaphysics of unity. It seems that without a radical transformation of ancient metaphysics (primarily Platonic and Aristotelian) a personalist interpretation of the Gospel becomes impossible.